From observers to authors: GGI solidifies Asian Century - Lee, Pei May (XINHUANET.com, 2025)
For decades, a handful of powers dictated the terms of global trade, security and development, often under the banner of multilateralism but in practice resorting to hierarchy and coercion. Disillusioned with this Western-dominated order, more in the world are finding a new vision proposed by China.